Crisis and Communitas Performative Concepts of Commonality in Arts and Politics - Sajewska, Dorota; Sugiera, Małgorzata (Routledge Advances in Theatre & Performance Studies, 2023)
This book is a critical, transdisciplinary examination of a broad range of philosophical ideas, theoretical concepts, and artistic projects of community in the 20th and 21st century in the context of global/local social and political changes. This volume opens new vitas by focusing on carefully selected instances of multipronged crises in which existing concepts of commonality are questioned, reformulated, or even speculatively designed with a (better) future in view. As many authors of this volume argue, in the face of today's unprecedented global ecological and economic challenges speculative design is of utmost importance as it can foster alternative, unthought-of forms of connectivity that go far beyond progressivist narratives of nation, corporation, and nuclear family. Focusing on the situations of upheaval, both historical and fabulated, the collection not only examines how multipronged crises trigger antagonisms between egalitarian forms of communitas and the normative concept of the nation (and other normative forms of communities) as a community that separates and excludes. It also looks closely at philosophical and artistic projects that strive to go beyond the dichotomies and typically extrapolated utopias, envisaging new political economies, ways of living and alternative relational structures. It will be of great interest to students and scholars in performance studies, cultural studies, political studies, media studies, postcolonial and decolonial studies, critical anthropology.